PHASE II DRUG METABOLIZING ENZYMES - Jancova, Petra; Anzenbacher, Pavel; Anzenbacherova, Eva (Biomedical papers, 2010)
Background: Phase II biotransformation reactions (also 'conjugation reactions') generally serve as a detoxifying step in drug metabolism. Phase II drug metabolising enzymes are mainly transferases. This review covers the major phase II enzymes: UDP-glucuronosyltransferases, sulfotransferases, N-acetyltransferases, glutathione S-transferases and methyltransferases (mainly thiopurine S-methyl transferase and catechol O-methyl transferase). The focus is on the presence of various forms, on tissue and cellular distribution, on the respective substrates, on genetic polymorphism and finally on the interspecies differences in these enzymes.Methods and Results: A literature search using the following databases PubMed, Science Direct and EBSCO for the years, 1969-2010.Conclusions: Phase II drug metabolizing enzymes play an important role in biotransformation of endogenous compounds and xenobiotics to more easily excretable forms as well as in the metabolic inactivation of pharmacologically active compounds. Reduced metabolising capacity of Phase II enzymes can lead to toxic effects of clinically used drugs. Gene polymorphism/ lack of these enzymes may often play a role in several forms of cancer.
Keywords: Phase II biotransformation/UDP-glucuronosyltransferases/Sulfotransferases; N-acetyltransferases/Glutathione-S-transferases/Thiopurine S-methyl transferase/Catechol O-methyl transferase